Evaluating the Effectiveness of Internal Auditing in Public Institutions in Morocco: An Accessible and Operational Approach. - EL AISSAOUI Hassan; OTMANE Youssef (African Scientific Journal, 2024)
Abstract The present work explores the effectiveness of internal audit within public institutions, focusing on its central role in improving governance. In this study, the evaluation of internal audit effectiveness is based on two categories of dimensions, incorporating specific variables. The internal dimension encompasses factors such as the skills and qualifications of internal auditors, the independence and objectivity of these auditors, quality management, the resources allocated to internal audit, the organizational culture, and communication and collaboration within the organization. The second category, the external dimension, examines factors such as the regulatory and normative framework, political pressures and external influences, the maturity level of governance and risk management, relationships with external stakeholders, and the evolution of the external context. Methodologically, the research adopts a pragmatic and accessible approach, combining a five-level rating scale with key indicators selected based on best theoretical practices in internal audit. Four public institutions (A, B, C, and D) are included in the sample, allowing for a rigorous evaluation across more than 61 criteria and 10 factors. The entire process, from data collection to comparative analysis, was designed to minimize operational burden while ensuring accuracy and relevance of the results. The main conclusion of this study is that this innovative methodology, which combines simplicity and rigor, enables a comprehensive and actionable assessment of internal audit effectiveness in an operational context, while making the results more understandable for decision-makers. Keywords : Internal Audit, Effectiveness, Governance, Stakeholder Relations, External Factors